Clinical Features, Management, and Prognostic Factors of Intracranial Solitary Fibrous Tumor - Liu, Jingdian; Wu, Sisi; Zhao, Kai; Wang, Junwen; Shu, Kai; Lei, Ting (Frontiers in Oncology, 2022)
Background: Due to the low incidence and the constantly changing diagnostic and classification criteria, the clinical features, management and prognostic factors of intracranial solitary fibrous tumor (ISFT) remain unclear and were thus analyzed in this study. Method: A total of 38 patients with ISFTs who were diagnosed in our institution were enrolled in this study. Patient data including age, gender, clinical presentation, histopathological features, immunohistochemistry staining, tumor location, tumor size, treatment methods, and prognosis were extracted and retrospectively analyzed. Results: The median age at diagnosis was 45.5 years (range 28-66 years) and the male to female ratio was 1:1.53 in our series. The 3-, 5-, and 10-year progression-free survival rate was 82.2%, 62.8%, and 21.4%, respectively; and the 3-, 5-, and 10-year overall survival rate was 97.1%, 86.9%, and 64.2%, respectively. Patients with high WHO grade (grade 3) ISFTs experienced impaired PFS (p<0.05) and OS (p<0.01). Subtotal resection (STR) was associated with worse PFS and OS (p<0.001, respectively). Postoperative radiotherapy (PORT) improved PFS, especially local control rate, in patients with WHO grade 3 ISFTs(P=0.025) or STR (p=0.027). Moreover, CD34-negative immunostaining and a high Ki-67 index (>10%) were associated with impaired PFS in ISFTs. Conclusion: Our study provides evidence that high tumor grade, subtotal tumor resection, CD34 negative immunostaining, and high Ki-67 index (>10%) were independent predictors for the poor prognosis of ISFTs. PORT can improve local control rate, and should be recommended for patients with high-grade ISFTs or STR.